De Éfeso ao Papa Francisco : um estudo comparativo entre a 1ª carta a Timóteo e a Evangelii Gaudium - Garcia, Diego Jobim (2020)
The present work proposes to draw a parallel between the 1ª Pastoral Letter sent to Timothy and the Encyclical Letter written by Pope Francis, emphasizing the clergy as the recipient of both. The research will present them, in their own historical environment, highlighting the main elements, recipients and characteristics that show the evangelizing action of the Church in its essence and also in its historical particularities. Finally, by highlighting similarities and differences between the two pastoral writings, we will present some aspects pertinent to the clergy, their strengths and weaknesses present in Timothy, but above all in the present Church, and some clues, so that the present priesthood finds its way in the mission of the Christ’s Church.